Customized training service with health and fitness tests for cyclic sports elite in post-COVID-19 rehabilitation period - Guba, V. P.; Marynich, V. V. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze the respiratory system functionality in the cyclic sports elite in the clinically monitored post-COVID-19 rehabilitation periods to offer training system customization options sensitive to the respiratory system health conditions. Methods and structure of the study. We sampled for the study the 19-22 year-old cyclic sports elite (n=16, including 6 males and 10 females) qualified CMS, MS and WCMS. The sample was tested four times per day as follows: (1) morning test; (2) post-aerobic-training test; (3) post-high-intensity (sub-maximal) anaerobic training test; and (4) rehabilitation-period test using a portable electrochemical NO-analyzer (NObreath, Bedfont Scientific Ltd.). The bronchial asthma and allergic rhinitis diagnosed individuals were excluded from the sample. Results and conclusion. An individual training system will be prudently managed with the workouts customized to the energy corridor of aerobic and anaerobic metabolism. There are good reasons to believe that the post-COV-ID-19 regress is due to a sort of `energy pits` with the athlete being unable to attain the pre-disease workloads within the anaerobic zone with the required anaerobic power. Premature transition in the anaerobic energy supply range in the early training process stages may expose the athletes to overstress risks, with regress in the functional fitness. The study found the elite cyclic sports sample being less tolerant to trainings within the anaerobic metabolism zone; and for this reason we recommended the training system being prudently customized to make a special emphasis on the aerobic capacity development practices dominated by breathing exercises including those facilitated by breath training machines. We also recommended expanding the range of medical services and functional fitness tests in the training process using special individualized medical/ biological support service protocols with a special attention to the elite athletes` functional fitness test data flow variations.